2013
DOI: 10.1093/ndt/gft036
|View full text |Cite
|
Sign up to set email alerts
|

What do we know about adenovirus in renal transplantation?

Abstract: Adenoviruses are common pathogens that have the potential to cause opportunistic infections with significant morbidity and mortality in immunocompromised hosts. The significance of adenoviral infection and disease is incompletely known in the setting of kidney transplantation. Reported adenovirus infections in renal transplant recipients have typically manifested as hemorrhagic cystitis and tubulointerstitial nephritis, less severe diseases than often seen in other solid organ transplant recipients (i.e. pneum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
73
1
13

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(87 citation statements)
references
References 54 publications
0
73
1
13
Order By: Relevance
“…Infections can be acquired de novo or via reactivation of latent virus from the recipient or the transplanted organ (157). The occurrence of adenoviremia has been reported to be less than 10% of adult patients after kidney, heart, or liver transplantation; although the symptoms of HAdV infection are usually mild, and invasive infection does not correlate with organ rejection (157), severe and even fatal courses have also been described (158,159). Studies in patients undergoing lung transplantation showed that pulmonary infection with HAdV can correlate with significantly elevated rates of rejection, bronchiolitis obliterans, and mortality (160)(161)(162).…”
Section: Incidence Of Hadv Infections In Immunocompromised Adult and mentioning
confidence: 99%
“…Infections can be acquired de novo or via reactivation of latent virus from the recipient or the transplanted organ (157). The occurrence of adenoviremia has been reported to be less than 10% of adult patients after kidney, heart, or liver transplantation; although the symptoms of HAdV infection are usually mild, and invasive infection does not correlate with organ rejection (157), severe and even fatal courses have also been described (158,159). Studies in patients undergoing lung transplantation showed that pulmonary infection with HAdV can correlate with significantly elevated rates of rejection, bronchiolitis obliterans, and mortality (160)(161)(162).…”
Section: Incidence Of Hadv Infections In Immunocompromised Adult and mentioning
confidence: 99%
“…Adenovirus is unique in that, although PCR is the preferred diagnostic test, negative testing from the upper or lower airway may not exclude infections. 13,14 Some assays detect some but not all of the serotypes. 14 Furthermore, adenovirus replication can occur in the absence of clinical symptoms and positive testing must be contextualized with the patients presenting signs and symptoms.…”
Section: Diagnosis Of Respiratory Viral Infectionsmentioning
confidence: 99%
“…Such pathology is helpful in distinguishing local infection (ie, adenovirus interstitial nephritis) from organ rejection or other pathology. 14…”
Section: Diagnosis Of Respiratory Viral Infectionsmentioning
confidence: 99%
“…Chez l'immunodé primé , les manifestations cliniques peuvent être graves. Bien que les complications virales soient une cause majeure de morbidité et de mortalité chez le transplanté ré nal, l'infection à adé novirus est peu fré quente [1][2][3][4][5][6].…”
Section: Introductionunclassified